Mining the social web : data mining facebook, twitter, linkedin, google+, github and more - Russell, Matthew A. (Beijing, China : O'Reilly Media, Incorporated, 2014)
This book has been carefully designed to provide an incredible learning experience for a particular target audience, and in order to avoid any unnecessary confusion about its scope or purpose by way of disgruntled emails, bad book reviews, or other misunderstandings that can come up, the remainder of this preface tries to help you determine whether you are part of that target audience.
Part I. A guided tour of the social web -- 1. Mining twitter : exploring trending topics, discovering what people are talking about and more -- 2. Mining facebook : analyzing fan pages, examining friendships and more -- 3. Mining linkedin : faceting job titles, clustering colleagues, and more -- 4. Mining google+ : computing document similarity, extracting collocations, and more -- 5. Mining web : using natural language processing to understand human language, summarize blog posts, and more -- 6. Mining mailboxes : analyzing who's talking to whom about what, how often and more -- 7. Mining GitHub : Inspecting software collaboration habits, building interest graphs, and more -- 8. Mining the semantically marked-up web : extracting microformats, inferencing over RDF, and more -- Part II. Twitter cookbook -- 9. Twitter cookbook.
Includes index.
Keywords: ELECTRONIC BOOKS